The construction of a new image of bodiness – the subculture of the third-age - Batsanova, Sophia V. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This article contains an analysis of the place of bodiness in the system of the third-age subculture. The author investigates the main components of the third-age subculture, her features and causes of her emergence. The problem of constructing of bodiness has been considered in terms of demand for certain types of bodiness in contemporary culture. The author especially stopped the attention on the new phenomenon of nakedness in aesthetics of contemporary oldness.